2004
DOI: 10.1038/nature02736
|View full text |Cite
|
Sign up to set email alerts
|

Fast delivery of meteorites to Earth after a major asteroid collision

Abstract: Very large collisions in the asteroid belt could lead temporarily to a substantial increase in the rate of impacts of meteorites on Earth. Orbital simulations predict that fragments from such events may arrive considerably faster than the typical transit times of meteorites falling today, because in some large impacts part of the debris is transferred directly into a resonant orbit with Jupiter. Such an efficient meteorite delivery track, however, has not been verified. Here we report high-sensitivity measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
120
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(139 citation statements)
references
References 21 publications
19
120
0
Order By: Relevance
“…The results of the EC searches are shown in There is no indication that changes in sedimentation rates, on average a few millimeter per thousand years, can explain the observed major trend in EC concentrations, although individual beds may have formed at different rates. That the disruption event 5 occurred in the lower L. variabilis Zone is consistent with cosmic-ray induced 21 Ne ages of chromite grains from the fossil meteorites 13 Some of the best sections for studies of Ordovician invertebrate diversification occur in Baltoscandia 23 . We have established the mid-Ordovician biodiversity trends for brachiopods based on bed-by-bed sampling of more than 30,000 fossils from eight sections in Baltoscandia (Fig.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…The results of the EC searches are shown in There is no indication that changes in sedimentation rates, on average a few millimeter per thousand years, can explain the observed major trend in EC concentrations, although individual beds may have formed at different rates. That the disruption event 5 occurred in the lower L. variabilis Zone is consistent with cosmic-ray induced 21 Ne ages of chromite grains from the fossil meteorites 13 Some of the best sections for studies of Ordovician invertebrate diversification occur in Baltoscandia 23 . We have established the mid-Ordovician biodiversity trends for brachiopods based on bed-by-bed sampling of more than 30,000 fossils from eight sections in Baltoscandia (Fig.…”
mentioning
confidence: 59%
“…In the limestone beds containing common meteorites also abundant chromite grains from decomposed micrometeorites are found [10][11][12] . Cosmic-ray induced 21 Ne in chromite from the fossil meteorites increases upward in the strata, supporting a common origin from an asteroid breakup event 13 . High-precision 40 Ar- 39 Ar dating of recent L chondrites has constrained the timing of their parent-body disruption to 470 ±6 Ma, which is identical within uncertainties to the age of 467.3 ±1.6 Ma for the beds with fossil meteorites according to the latest geologic time scale 14 .…”
mentioning
confidence: 97%
“…Oxygen isotope data on chromites ) as well as petrographic evidence ) further support the L-chondrite classification of these fossil meteorites. Chromite proved to be retentive for cosmogenic (and in one case also for solar) noble gases (Heck et al 2003(Heck et al , 2004. Heck et al (2004) showed that the transfer times of the fossil L chondrites from their parent body to Earth, measured by cosmogenic noble gases, were unusually short compared to the transfer times of modern ordinary chondrites-only between 0.1-1 Myr.…”
Section: Introductionmentioning
confidence: 99%
“…Chromite proved to be retentive for cosmogenic (and in one case also for solar) noble gases (Heck et al 2003(Heck et al , 2004. Heck et al (2004) showed that the transfer times of the fossil L chondrites from their parent body to Earth, measured by cosmogenic noble gases, were unusually short compared to the transfer times of modern ordinary chondrites-only between 0.1-1 Myr. Furthermore, ages increase with decreasing sediment age (Heck et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For further details on the instrument, analytical procedures 127 and calculations, see Heck et al (2004Heck et al ( , 2008 and Meier et al (2010). 128…”
mentioning
confidence: 99%